2021
DOI: 10.31235/osf.io/4atj7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expectations after expecting: the impact of first birth on the fertility expectations of one child women in the USA and UK

Abstract: Expectations for having children are hypothesised to be predominantly influenced by societal family norms at young ages, and are adjusted during the life course in response to changing circumstances and new information. The onset of parenthood is likely to be a key event that affects expectations. This paper explores whether the expectations of women who have only one child (one child women) change in the five years before and after first birth, using the National Longitudinal Survey of Youth 1979 (USA) and Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…A short-term fertility intention is generally considered as a plan of action to have a child in the near future, with the underlying rationale that an intention will be indicative of subsequent behaviour, considering the perceived costs and benefits of having children (Ajzen & Klobas, 2013;Raybould & Sear, 2021). The literature uses different definitions of uncertainty in fertility intentions (Kuhnt et al, 2021) and previous research has demonstrated the importance of uncertainty and change in overall intentions (e.g., Jones, 2017;Kuhnt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A short-term fertility intention is generally considered as a plan of action to have a child in the near future, with the underlying rationale that an intention will be indicative of subsequent behaviour, considering the perceived costs and benefits of having children (Ajzen & Klobas, 2013;Raybould & Sear, 2021). The literature uses different definitions of uncertainty in fertility intentions (Kuhnt et al, 2021) and previous research has demonstrated the importance of uncertainty and change in overall intentions (e.g., Jones, 2017;Kuhnt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%